2018
DOI: 10.1007/s13157-018-1019-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of the Carbon and Nitrogen Isotopic Signature in a Zostera noltei Meadow at the NW Iberian Peninsula

Abstract: Nitrogen (N) and carbon (C) isotopic analyses in seagrasses have been established as effective environmental tracers to assess the anthropogenic influence on seagrass meadows. The aim of this study was to determine the spatial patterns and seasonal variability in the C and N stable isotopic composition of sediments, leaves and epiphytes at a Zostera noltei meadow in an intertidal complex located at the Ría de Vigo (NW Iberian Peninsula) and to explore the mechanisms underlying such variability.Measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
2
5
0
Order By: Relevance
“…Surface dissolved nitrogen concentrations (DIN) and isotopic discrimination for δ 15 N in Ría de Vigo are typically higher from October to April, decreasing from May to September [ 60 ]. Hence, higher δ 15 N signatures in spring–summer would be expected [ 78 , 79 ]. The opposite trend would occur in δ 13 C signatures [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surface dissolved nitrogen concentrations (DIN) and isotopic discrimination for δ 15 N in Ría de Vigo are typically higher from October to April, decreasing from May to September [ 60 ]. Hence, higher δ 15 N signatures in spring–summer would be expected [ 78 , 79 ]. The opposite trend would occur in δ 13 C signatures [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…noltei leaves were not acidified. Previous acidification experiments carried out with samples from A Ramallosa (Román et al, 2018), showed that δ 13 C ratios did not show significant differences between acidified (δ 13 C = -14.0 ± 0.5 ‰) and non-acidified (δ 13 C = -14.0 ± 0.7 ‰) Z. noltei samples (p>0.05, n= 5), suggesting that the amount of carbonates attached to these leaves are likely to be negligible. (Sulzman, 2007).…”
Section: Isotopic Analysismentioning
confidence: 84%
“…Since the Z. noltei samples were collected at different seasons, the biological fractionation exerted by the plant and the epiphytes caused by seasonality can alter the isotopic ratios and complicate a straightforward interpretation of the observed isotopic signatures on the basis of anthropogenic nitrogen inputs (Román et al, 2018).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Indeed, a relevant fraction of the nitrogen present in seagrass meadows is originated by the decay and decomposition of seagrass leaves (Lee et al, 2007). So this recycling process, jointly with the inputs of matter into the meadow, can modulate the δ N in the sediments, partially explaining the observed correlation between δ N in sediments and in Z. noltei (Román et al, 2018).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%